Ultrasonic control of marine fouling - T S Gughan (2018)
Biofouling occurs when marine organisms adhere to and colonise underwater surfaces. It is highly prevalent in the marine industry where ship hulls are often coated by layers of biofouling, resulting in loss of hydro-dynamicity and increased fuel consumption. Ship owners have been painting ship hulls with antifouling paints laced with biocides in hoped of deterring biofouling. But recent concerns over the dangers these paints and biocides pose to the environment has led to alternative modes of antifouling being adopted in the marine industry. Research has shown the effectiveness of ultrasonic waves in inhibiting the formation of biofouling and as such, commercial ultrasonic antifouling systems have been designed for use of marine vessels. However these systems lack the energy efficiency required for use on larger vessels. In this project, an energy efficient ultrasonic antifouling system was designed and assembled to fill the abovementioned niche in the industry. The system uses ultrasonic waves of a frequency of 100 kHz, vibrating in the shear horizontal mode. These waves are cyclically operated with a relay to allow for a larger area of antifouling coverage for a lesser power consumption. This project is part of an ongoing effort by Nanyang Technological University’s School of Mechanical and Aerospace Engineering to create an efficient ultrasonic antifouling system which poses little to no risk to the environment.